2023
DOI: 10.1136/bmjopen-2022-068811
|View full text |Cite
|
Sign up to set email alerts
|

Study profile: the Genetics of Glaucoma Study

Abstract: PurposeGlaucoma, a major cause of irreversible blindness, is a highly heritable human disease. Currently, the majority of the risk genes for glaucoma are unknown. We established the Genetics of Glaucoma Study (GOGS) to identify disease genes and improve genetic prediction of glaucoma risk and response to treatment.ParticipantsMore than 5700 participants with glaucoma or a family history of glaucoma were recruited through a media campaign and the Australian Government healthcare service provider, Services Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Its pathogenesis is related to various genetic mutations and somatic diseases, indicating that glaucoma is a complicated genetic disorder ( Wändell et al, 2022 ). Specifically, it was found that primary open-angle glaucoma (POAG) is highly heritable with 70% of the variation in risk attributed to genetics ( Gharahkhani et al, 2023 ). To date, clinically, the causing factors contributing to glaucoma progression are still not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Its pathogenesis is related to various genetic mutations and somatic diseases, indicating that glaucoma is a complicated genetic disorder ( Wändell et al, 2022 ). Specifically, it was found that primary open-angle glaucoma (POAG) is highly heritable with 70% of the variation in risk attributed to genetics ( Gharahkhani et al, 2023 ). To date, clinically, the causing factors contributing to glaucoma progression are still not well characterized.…”
Section: Introductionmentioning
confidence: 99%